FRI0421 What Is The Location of Enthesitis in Ankylosing Spondylitis and Psoriatic Arthritis Patients and How Do They Respond To Anti-TNF Treatment?. (15th July 2016) - Kelsall, J.; Choquette, D.; Rahman, P.; Arendse, R.; Teo, M.; Fortin, I.; Avina-Zubieta, J.A.; Rampakakis, E.; Psaradellis, E.; Maslova, K.; Osborne, B.; Tkaczyk, C.; et al.
Abstract : Background: Enthesitis is characterized by inflammation at the insertion of ligaments, tendons, joint capsule, or fascia to bone, and represents a well-known characteristic feature of ankylosing spondylitis (AS) and related spondyloarthropathies. Objectives: To identify the location of enthesitis in ankylosing spondylitis (AS) and psoriatic arthritis (PsA) patients and to determine their response to anti-TNF treatment. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis, AS, or psoriatic arthritis (PsA) with infliximab (IFX) or golimumab (GLM). Eligible people for this analysis included AS and PsA patients treated with IFX who were enrolled since 2005 or with GLM enrolled since 2010 who had available information on enthesitis. The paired sampled t-test was used to compare the enthesitis count at baseline and 12 months. Results: A total of 260 AS patients and 261 PsA patients were enrolled with a mean (SD) age at baseline of 46.1 (13.0) vs. 50.0 (12.0) years, respectively, and disease duration of 6.4 (9.8) vs. 5.2 (6.8) years. Among patients with AS, 28.1%, 21.7%, 22.4% had enthesitis at baseline, 6 months and 12 months, respectively. For PsA these numbers were 32.2%, 19.7%, and 22.6%, respectively. The presence of enthesitis by anatomical site and visit are described in Table 1 with higher proportions observed for the greater trochanter (GT) in AS patients and the lateral epicondyle humerus (LEH) in PsA patients. Presence of enthesitis in all anatomical sites was significantly associated with higher HAQ among AS and PsA patients. The mean (SD) enthesitis count at baseline and 12 months was 4.4 (3.4) vs. 2.6 (2.3) (P=0.061) among AS patients and 5.0 (3.8) vs. 3.8 (3.0) (P=0.006) in PsA patients, respectively. Conclusions: A considerable proportion of PsA and AS patients had enthesitis at anti-TNF initiation in this Canadian real-world cohort. Overall, presence of enthesitis was associated with significantly higher functional disability. Treatment with IFX or GLM for 12 months was associated with significant reduction in the mean enthesitis count. Disclosure of Interest: J. Kelsall: None declared, D. Choquette: None declared, P. Rahman: None declared, R. Arendse: None declared, M. Teo: None declared, I. Fortin: None declared, J. A. Avina-Zubieta: None declared, E. Rampakakis: None declared, E. Psaradellis: None declared, K. Maslova Employee of: Janssen Inc., B. Osborne Employee of: Janssen Inc., C. Tkaczyk Employee of: Janssen Inc., F. Nantel Employee of: Janssen Inc., A. Lehman Employee of: Janssen Inc.